(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The general goal of monitoring hazardous phenomena and processes in nature and the technosphere is to improve the accuracy and reliability of forecasting emergencies by combining the intellectual, information and technological capabilities of various departments and organizations involved in monitoring certain types of hazards. Monitoring data serve as the basis for forecasting. In the general case, forecasting is a creative research process, as a result of which hypothetical data about the future state of an object, phenomenon, process are obtained.